CODE MIXING USED IN THE ARTICLES OF ONLINE MEDIA NEWS KABAR MEDAN - Tiara Arianto; Diana Sopha (Fakultas Sastra UMN AL Washliyah, 2022)
Code mixing is changing one language into another during a conversation or in a written or spoken text. The data used in this research is the article Kabar Medan 2021 edition as many as 35 articles. This study aims to find out how the form of code-mixing is found in news articles in Kabar Medan and to find the dominant type that appears in the articles under study. The method used is a qualitative method. In this study, the researcher used several steps to analyze the data, namely reading the article, identifying words related to the article in Kabar Medan and containing code mixing, classifying the types of code mixing, describing the data and finally making conclusions. The results of this study indicate that there are 3 types of code mixing based on the theory, namely (Insertion, Alternation, and Congruent Lexicalization). Researchers found 105 data, including insertion of 89 words, Alternation of 4 words, and Congruent Lexicalization of 12 words. Based on the calculation results, the researcher concludes that Insertion is the dominant type of code mixing that appears in the Kabar Medan news article.